Ozualdo Candeias e a representação das mulheres nos filmes Aopção ou As Rosas da estrada e As bellas da Billings - Santos, Susana Aparecida dos (Universidade Federal de São Carlos, 2021)
This dissertation investigates the films Aopção ou As rosas da estrada (1981) and As bellas da Billings (1986), directed by Ozualdo Candeias. Through film analysis, articulated with the concepts of feminist and gender theory, the research focus on the construction of female characters in both films. The central concern is to discuss the construction of the characters through cinematographic resources, relying on gender theories, thus valuing the ambiguity of the representations. We also seek to relate the representation of women in these films with Candeias’ other works and with Boca do Lixo.
Ozualdo Candeias and the women's representation in Aopção ou As Rosas da estrada and As bellas da Billings
Keywords: Gênero; Personagens femininas; Análise fílmica; Ozualdo Candeias; Boca do Lixo; Gender; Female characters; Film analysis; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO